The Molecular Mechanism of Aerobic Exercise Improving Vascular Remodeling in Hypertension - Song, Yinping; Jia, Hao; Hua, Yijie; Wu, Chen; Li, Sujuan; Li, Kunzhe; Liang, Zhicheng; Wang, Youhua (Frontiers in Physiology, 2022)
The treatment and prevention of hypertension has been a worldwide medical challenge. The key pathological hallmark of hypertension is altered arterial vascular structure and function, i.e., increased peripheral vascular resistance due to vascular remodeling. The aim of this review is to elucidate the molecular mechanisms of vascular remodeling in hypertension and the mechanisms of aerobic exercise for the protection of vascular remodeling in hypertension. The main focus is on the mechanisms of oxidative stress and inflammation in the pathological condition of hypertension and vascular phenotypic transformation induced by the trilaminar structure of vascular endothelial cells, smooth muscle cells and extracellular matrix and the peripheral adipose layer of the vasculature. The possible mechanisms of aerobic exercise intervention to improve vascular remodeling in hypertension through anti-value-added, anti-inflammatory inhibition of vascular phenotypic transition were further explored. It provides a new perspective to reveal the intervention targets of vascular remodeling for the prevention and treatment of hypertension and its complications.